1984
DOI: 10.1007/bf00219860
|View full text |Cite
|
Sign up to set email alerts
|

Localization and function of cyclic guanosine monophosphate-phosphodiesterase activity in the retinal rods of the rat by means of a newly developed cytochemical method

Abstract: Cyclic guanosine monophosphate-phosphodiesterase (cGMP-PDEase) activity was studied histo- and cytochemically in the retinal rods of the rat with the use of a newly developed technique. Intense activity of cGMP-PDEase was evenly distributed over the outer segments of the rods. Reaction product was observed on the plasmalemma and on the disk membranes of the outer segments. A weak reaction product occurred also on the plasmalemma of the inner segments; however, no precipitate was found in the perinuclear and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In conventional enzyme cytochemistry, the reaction product of PDEase was reported to be observed on the disc membranes of the outer segments (12,13,19). In our study, the precipitate was clearly shown in the cisternal space of the disc membrane in the rod outer segment after conventional fixation (Fig.…”
Section: Penetration Of Purified 5'-nase Into the Tissuessupporting
confidence: 55%
See 2 more Smart Citations
“…In conventional enzyme cytochemistry, the reaction product of PDEase was reported to be observed on the disc membranes of the outer segments (12,13,19). In our study, the precipitate was clearly shown in the cisternal space of the disc membrane in the rod outer segment after conventional fixation (Fig.…”
Section: Penetration Of Purified 5'-nase Into the Tissuessupporting
confidence: 55%
“…The use of snake venom introduced two major difficult problems. 1) Snake venom destroyed the cell ultrastructure owing to enzymes such as protease and lipases included in the snake venom (17,19).…”
Section: Penetration Of Purified 5'-nase Into the Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many components of the NO-cGMP signaling pathway (supplemental Fig. 1, available at www.jneurosci.org as supplemental material) are present in photoreceptors: nitric oxide synthase (NOS) is present in cone and rod inner segments, the surrounding horizontal neurons, and Müller glia cells (Liepe et al, 1994;Haberecht et al, 1998); protein kinase G (PKG) type I and possibly type II are present in photoreceptor inner segments and the outer synaptic layer where photoreceptor terminals lie (Gamm et al, 2000); and cGMP-phosphodiesterase (PDE) is present in outer segments but also rod inner segments (Ueno et al, 1984). At present, sGC protein has been observed only in cone cells (Haberecht et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The outer segments of the rod are packed by parallel membranes on which the visual pigments and cGMP metabolizing enzymes are supposed to localize (48). These arrangements of enzymes on the rod outer segment are of histochemical interest (5,6,25,26,30,39,(40)(41)(42)46), because such detailed visualization of the efficient metabolism has yet to be reported. The tool to so visualize the exact active enzyme sites is rapid freeze enzyme CORRESPONDING ADDRESS: Takuma Saito, Department of Anatomy, Jichi Medical School, 3311 Yakushiji, Minamikawachi-machi, Kawachi-gun, Tochigi 329-04.…”
mentioning
confidence: 99%